Optimizing management accounting: strategies for clear communication, cost efficiency, and timely reporting - Azman, Alia Hanim; Abd Razak, Siti Noor Azmawaty (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Management accounting is a critical function that supports strategic decision-making by providing financial insights tailored for internal managerial use. However, challenges such as communication barriers, cost constraints, and time-sensitive reporting requirements hinder its effectiveness. This paper examines these key issues and explores practical solutions to enhance management accounting processes. It highlights the importance of clear financial communication, strategic cost management, and timely reporting to optimize decision-making. The study emphasizes the role of financial literacy, digital transformation, and automation including artificial intelligence (AI) and enterprise resource planning (ERP) systems—in addressing these challenges. By adopting these strategies, organizations can improve the accuracy, efficiency, and accessibility of management accounting information, ultimately strengthening financial planning and business performance. As businesses transition into Industry 4.0, integrating advanced technologies in management accounting will be crucial for maintaining a competitive edge.